Counterculture Of 1960-S and «Underground Press» in the Usa - Vyacheslavovich Bodrov, Oleg (2021)
The Underground Press Syndicate (UPS), later known as Alternative Press Syndicate (APS), was a chain of countercultural newspapers and magazines created in the middle of 1966 by publishers of five early underground newspapers «The East Village Other», «The Los Angeles Free Press», «The Berkeley Barb», «The Paper» and «Fifth Estate». By 1974 the majority of underground papers in the USA ceased to exist but  they had an impact on journalistic processes during 1970-s that led to the press development in small towns and countryside giving alternative opinion about local news, cultural news, Native Americans’ politics, ecology, youth and anti-military movements. The article considers the history of “underground press” in the USA, its role and importance for Countercultural Revolution of the 1960-s, which was countrywide in the USA and covered all areas of life.